2-Photon Characterization of Optical Proteolytic Beacons for Imaging Changes in Matrix-Metalloprotease Activity in a Mouse Model of Aneurysm. (23rd February 2016) - Haskett, Darren G.; Maestas, David; Howerton, Stephen J.; Smith, Tyler; Ardila, D. Catalina; Doetschman, Tom; Utzinger, Urs; McGrath, Dominic; McIntyre, J. Oliver; Vande Geest, Jonathan P.
Abstract: Abdominal aortic aneurysm is a multifactorial disease that is a leading cause of death in developed countries. Matrix-metalloproteases (MMPs) are part of the disease process, however, assessing their role in disease initiation and progression has been difficult and animal models have become essential. Combining Förster resonance energy transfer (FRET) proteolytic beacons activated in the presence of MMPs with 2-photon microscopy allows for a novel method of evaluating MMP activity within the extracellular matrix (ECM). Single and 2-photon spectra for proteolytic beacons were determined in vitro . Ex vivo experiments using the apolipoprotein E knockout angiotensin II-infused mouse model of aneurysm imaged ECM architecture simultaneously with the MMP-activated FRET beacons. 2-photon spectra of the two-color proteolytic beacons showed peaks for the individual fluorophores that enable imaging of MMP activity through proteolytic cleavage. Ex vivo imaging of the beacons within the ECM revealed both microstructure and MMP activity. 2-photon imaging of the beacons in aneurysmal tissue showed an increase in proteolytic cleavage within the ECM ( p <0.001), thus indicating an increase in MMP activity. Our data suggest that FRET-based proteolytic beacons show promise in assessing MMP activity within the ECM and will therefore allow future studies to identify the heterogeneous distribution of simultaneous ECM remodeling and protease activity in aneurysmal disease.